2007
DOI: 10.1002/adma.200701141
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogel‐Encapsulated Microfabricated Haircells Mimicking Fish Cupula Neuromast

Abstract: A hydrogel‐capped hair‐cell flow microsensor, which closely mimics a superficial neuromast of a fish, is introduced. By encapsulating the hair sensor into the artificial hydrogel cupula a dramatic increase in hair‐sensor sensitivity to the oscillating and the steady flow is achieved. It opens the way toward the remote monitoring of the underwater environment by autonomous, unmanned microvehicles with self‐navigating capability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
153
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(158 citation statements)
references
References 35 publications
4
153
1
Order By: Relevance
“…SFS provides a force spectrum with pico-Newton precision, nano-Newton applied forces and nanoscale deflections ( Tsukruk et al 2000). SFS has already been proven to be an invaluable tool for studying biological receptors and the structures associated with them (Fuchigami et al 2001;Gorbunov et al 2002;McConney et al 2007;Peleshanko et al 2007). Here, we report on a methodology that combines representing the suspension of a trichobothrium as a linear viscoelastic material with direct measurements to determine the values of the three-parameter and two-parameter viscoelastic models explored.…”
Section: Introductionmentioning
confidence: 99%
“…SFS provides a force spectrum with pico-Newton precision, nano-Newton applied forces and nanoscale deflections ( Tsukruk et al 2000). SFS has already been proven to be an invaluable tool for studying biological receptors and the structures associated with them (Fuchigami et al 2001;Gorbunov et al 2002;McConney et al 2007;Peleshanko et al 2007). Here, we report on a methodology that combines representing the suspension of a trichobothrium as a linear viscoelastic material with direct measurements to determine the values of the three-parameter and two-parameter viscoelastic models explored.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the demonstrated unique capability of our approach to create nanostructures with elliptical cross-sections makes it possible to design a truly biomimetic sensor that responds to an anisotropic flow field in a manner, similar to cilia in fish and amphibians. [13] In this case, the moment of inertia in the directions of the two radii will be: I 1 = πr 1 3 r 2 /4 and I 2 = πr 1 r 2 3 /4, and for the given force, the deflection in the direction of r 1 compared to r 2 scales as (r 2 /r 1 ) 2 .…”
mentioning
confidence: 99%
“…While nanostructured superhydrophobic surfaces inspired by the lotus flower and the adhesive properties of gecko feet have been mimicked with success, [10][11][12] actuation/sensing at the submicron scale is a challenging goal. Sensor arrays inspired by fish skin [13] are still lacking the key features related to their selectivity, tunable geometry and sensitivity. We have recently demonstrated that by using a hydrogel muscle one can reversibly actuate Si nanostructures, which dynamically change their orientation in response to humidity, with a 60 ms response time.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…glucose), [18] or pH. [19] To gain additional control over bending orientation, beyond what is achievable by topographically patterned hydrogel, we can utilize principles of symmetry breaking found in nature-such as the asymmetric distribution of growing actin filaments allowing for uni-directional cellular motion [20] or the oval cross-sections of cilia on the bodies of fish and amphibians enabling sensing of anisotropic flow fields [21,22] -and design asymmetric actuators which support anisotropically shaped structures that may limit motion to only desired directions. We present here a novel bio-inspired surface operating in a fluidic environment for which reversible actuation of embedded skeletal elements is generated by the Submitted to 3 chemo-mechanical response of a pH-sensitive hydrogel over large areas with controlled patterns and direction of actuation.…”
mentioning
confidence: 99%